Pengembangan Media Pembelajaran Domino Card untuk Mata Pelajaran Dasar-Dasar Akuntansi dan Keuangan Lembaga - Leony Devi Antika Sar; Budi Mulyati; Yusina Fadla Ilmi; Fitri Nurlaili; Anggi Haerani; Khristina Sri Prihatin (FKIP, Universitas Banten Jaya, 2026)
This research is conducted based on the results of a learning needs analysis collaborated with teachers at a vocational high school. Several obstacles were found in the learning process, including the suboptimal use of learning resources and the unavailability of game-based learning media at school. This study aims to develop domino card learning media for 11th grade vocational high school students in learning the basics of accounting and institutional finance. This study used R&D (Research & Development) method with 4D model. The stages of this model include define, design, develop, and disseminate. The results showed that the domino card media was suitable for use based on the assessment results from the validators, namely the material expert gave a score of 90.66%, the media expert gave a score of 92% and the learning design expert gave a score of 100%, and all three are in the very suitable category. The response from users gave very good results, where students gave a response with a score of 80% and teachers gave a response with a score of 100%. Therefore, it can be said that the domino card media developed in this study is suitable for use in the learning process at vocational school for the subject of basic accounting and institutional finance.